The Influence of Religious Value Comprehension on Social Tolerance Among Elementary School Students - Mutiara, Yolanda; Shintia, Alfira Mersania; Mulyana, Windu Damar; Refaldi, Agung Agus (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This study aims to determine the effect of understanding religious values on the social tolerance of sixth-grade students at SDIT Az-Zikro. This study uses a quantitative approach with a correlational method. The study population was all 25 sixth-grade students, with a sample of 15 students selected purposively. The research instrument was a validated Likert-scale questionnaire. The results of the analysis indicate that understanding religious values has a positive influence on students' social tolerance. The better the understanding of religious values, the higher their tolerance in the school environment.